Bringing taxonomy to school kids: Aedokritus adotivae sp. n. from Amazon (Diptera: Chironomidae) - Pinho, Luiz Carlos (Zootaxa, 2018)
Children curiosity about how taxonomy works led me to ask for their help to choose a name for a new species of Aedokritus Roback from Pará State (Brazilian Amazon). Aedokritus adotivae sp. n. is here described based on male adults. A key to species of the genus is provided.